DETECTION OF Salmonella sp. IN PACKAGED SALMON SASHIMI FROM SEVERAL RETAIL OUTLETS IN BANDUNG CITY - Balqis Aliya Zain; Evi Liviawaty; Iis Rostini; Rusky Intan Pratama (Universitas Mataram, 2025)
Sashimi is a Japanese culinary dish consisting of raw fish slices. This study aims to determine the potential contamination of Salmonella sp. bacteria and the freshness level of packaged salmon sashimi through chemical parameters such as TVB-N and pH, as well as organoleptic characteristics including meat appearance, aroma, and texture as observation parameters. Three samples of packaged salmon sashimi were obtained from three different sales locations in Bandung City. Salmonella sp. bacteria detection was performed using Salmonella Shigella Agar as the bacterial isolation medium. TVB-N was tested using SNI 2354-8-2009 as the testing reference, while pH was measured using a pH meter. Organoleptic characteristics were observed by scoring tests conducted by 20 semi-trained panelists using the SNI 2693:2014 score sheet, and the results were calculated using the scoring test formula in accordance with SNI 01-2346-2006. The results of the Salmonella sp. detection, TVB-N, and pH tests were analyzed descriptively and quantitatively. The results showed that no Salmonella sp. contamination was detected in the three packaged salmon sashimi samples. The pH values ranged from 6.45 to 6.47 and TVB-N from 3.33 to 6.58 mg/100g, with all three samples still in the fresh category. Organoleptically, sample B met the freshness quality standards for sashimi products.